Pendampingan dan Implementasi Projek Penguatan Profil Pelajar Pancasila (P5) Dimensi Berkebinekaan Global Dengan Tema Suara Demokrasi di SMPN 5 Pangean - Adilla, Putri; Hadi Purwanto; Sarwan, Sarwan; Mutia Risma (Jurnal Pengabdian UntukMu NegeRI, 2024)
The implementation of the Pancasila (P5) Student Profile Strengthening Project with the theme "Democratic Voice" at SMPN 5 Pangean aims to introduce and strengthen democratic values among students. In the context of the independent curriculum, which prioritises project-based learning to develop character and skills, this activity integrates democratic principles with practical experience in the general election process. The implementation method consists of a theory session on the concept of democracy and election, followed by a general election simulation, as well as post-activity analysis to ensure student understanding and involvement. The results of the evaluation showed that the students succeeded in understanding and carrying out the election simulation well, without the presence of golput participants, and showed a deep understanding of the democratic process and Pancasila values. This activity has proven to be effective in increasing students' knowledge of democracy and preparing them to actively participate in future elections.